Pengembangan Keahlian dalam Produksi Kopi Liwa Melalui Pelatihan Penggunaan Mesin - M. Yusuf S Barusman; Hendri Dunan; Niki Agus Santoso; Aprinisa Aprinisa; Appin Purisky Redaputri (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2024)
Training on using coffee machines was held to improve the skills of Gamba Kupi Liwa Community members in the coffee production process. Through a theoretical and practical approach, participants are introduced to the concept of using modern machines to increase the efficiency and quality of coffee products. Training involves theory sessions, practical demonstrations, as well as interactive discussions. The training methodology includes exposure to the basic concepts of using coffee machines, hands-on practical sessions using modern equipment, and case studies to demonstrate the application of concepts in the coffee industry. The evaluation was carried out to measure participant understanding and the impact of the training on Gamba Kupi Liwa Community coffee production. The results of the training showed significant improvements in machine usage skills, operational efficiency and product quality. Additionally, training creates a collaborative environment among community members, increasing their involvement in the development of the local coffee industry. Thus, this training not only develops technical skills, but also builds the foundation for sustainable growth in the coffee industry. The success of this training provides a positive view of the potential of the Gamba Kupi Liwa Community to become a major player in the coffee industry, creating a positive impact on the community's economy and society.